Shifting gears : exploring the mobility stories of Latin American women in Auckland : a dissertation presented in partial fulfilment of the requirements for the degree of Master of Resource and Environmental Planning at Massey University, Aotearoa New Zealand - Rodriguez Mora, Anamaria (Massey University, 2025)
Increasing immigration presents Aotearoa New Zealand with both challenges and opportunities for its transport system. While Aotearoa’s cities aspire to encourage the use of low-carbon transport modes (walking, cycling and public transport), a key challenge to this transition is the ongoing 'reverse mode shifts' (RMS); where immigrant women shift from using low-carbon transport in their respective countries to private cars after migrating. Given the sharp growth of immigrants in Auckland, understanding this phenomenon is key to plan for the future of its transport system. This thesis explores the factors that encourage or discourage Latin American women in Auckland to RMS after migration, and proposes ways to discourage immigrant women from embracing driving after migration. This research uses the ’new mobilities paradigm’(NMP) as a theoretical framework, to understand the mobility challenges immigrant women face daily, and identify key ways of progressing sustainability and equity planning outcomes. Specifically, the research applies Tim Cresswell’s (2010) framework, which is informed by the NMP, to explore how social and power dynamics play a part in the emergence of new patterns of (im)mobility, leading Latin American to RMS after migration. The thesis takes a qualitative research approach, combining two sources of data. First, the thesis involves a critical review of the planning framework by reviewing documents relevant to transport planning in Auckland. Second, over twenty Latin American women residing in Auckland were interviewed to capture their (im)mobility experiences through stories. The findings revealed that Latin American women are encouraged to embrace driving as a way to address inequalities linked to Auckland’s transport system. Driving is a means for them to offset economic, socio-cultural and physical obstacles in the city. The research shows driving is not necessarily a choice in a car-dependent city like Auckland, as many would not choose to drive If they had alternative and sustainable options. Key factors influencing their RMS included motherhood (i.e. having a baby), needing to work in a sprawled city and desires to feel free, independent and equal. However, perceptions of fear, anxiety and stress when driving discouraged several participants from driving as main commuting mode. Although some of them found ways to either manage or accept these barriers, the perceptions of fear, anxiety and stress remain present for most, suggesting Latin American women end up sacrificing their mobilities experiences to fulfil other needs. The research concludes that the RMS of immigrant women in Auckland are strongly influenced by to transport planning approaches adopted in the city. These approaches prioritise economic growth and individual market choice over sustainability and equity-needs-approaches which ultimately promoted forced car ownership and usage. The research recommends prioritising transport planning approaches that understands human as experiential and emotional beings, moving away from approaches centred on rational philosophies. This research sits between social science and applied planning and have advance theoretical and practical knowledge that emphasis the needs of alternative approaches in transport planning to address the mobility challenges of immigrant women.
Figure 8 is ©2023 Auckland Council but reused under a Creative Commons Attribution 4.0 International licence. Figure 10 (=Mattingly & Morrissey, 2014, Fig 4) was removed. Figure 11 is ©2017 Greater Auckland and was removed, but may be accessed at https://www.greaterauckland.org.nz/2024/10/07/2023-census-travel-to-work-results/
Keywords: mobilities; transport; immigration; equality; sustainability; 330409 Transport planning; 441016 Urban sociology and community studies